Biomarker distributions in surface sediments from the Kara and Laptev seas (Arctic Ocean): indicators for organic-carbon sources and sea-ice coverage. - Xiao, Xiaotong; Fahl, Kirsten; Stein, Ruediger (PANGAEA, 2013)
Studies of spatial and temporal changes in modern and past sea-ice occurrence may help to understand the processes controlling the recent decrease in Arctic sea-ice cover. Here, we determined concentrations of IP25, a novel biomarker proxy for sea ice developed in recent years, phytoplankton-derived biomarkers (brassicasterol and dinosterol) and terrigenous biomarkers (campesterol and ß-sitosterol) in the surface sediments from the Kara and Laptev seas to estimate modern spatial (seasonal) sea-ice variability and organic-matter sources. C25-HBI dienes and trienes were determined as additional paleoenvironmental proxies in the study area. Furthermore, a combined phytoplankton-IP25 biomarker approach (PIP25 index) is used to reconstruct the modern sea-ice distribution more quantitatively. The terrigenous biomarkers reach maximum concentrations in the coastal zones and estuaries, reflecting the huge discharge by the major rivers Ob, Yenisei and Lena. Maxima in phytoplankton biomarkers indicating increased primary productivity were found in the seasonally ice-free central part of the Kara and Laptev seas. Neither IP25 nor PIP25, however, show a clear and simple correlation with satellite sea-ice distribution in our study area due to the complex environmental conditions in our study area and the transportation process of sea-ice diatom in the water column. Differences in the diene/IP25 and triene/IP25 ratios point to different sources of these HBIs and different environmental conditions. The diene/IP25 ratio seems to correlate positively with sea-surface temperature, while negatively with salinity distributions.
Biomarker distributions in surface sediments from the Kara and Laptev Seas (Arctic Ocean)
Keywords: 2,10,14-Trimethyl-6-enyl-7-(3-methylpent-1-enyl)pentadecene per unit mass total organic carbon; 24-Ethylcholest-5-en-3beta-ol per unit mass total organic carbon; 24-Methylcholest-5-en-3beta-ol per unit mass total organic carbon; 24-Methylcholesta-5,22E-dien-3beta-ol per unit mass total organic carbon; 4alpha,23,24-Trimethyl-5alpha-cholest-22E-en-3beta-ol per unit mass total organic carbon; Akademik Boris Petrov; Arctic Ocean; ARK-XI/1; ARK-XXVI/3; AWI_Paleo; BP00; BP00-02; BP00-04; BP00-05; BP00-07; BP00-08; BP00-09; BP00-13; BP00-14; BP00-15; BP00-16; BP00-17; BP00-22; BP00-23; BP00-26; BP00-27; BP00-28; BP00-29; BP00-30; BP00-31; BP00-35; BP00-36; BP00-38; BP01; BP01-38; BP01-43; BP01-64; BP01-67; BP01-73a; BP01-74; BP01-75; BP01-76; BP01-78; BP01-79; BP02; BP02-01B; BP02-02B; BP02-03/01; BP02-05/01; BUCKET; Bucket water sampling; C25 highly branched isoprenoid diene/IP25 ratio; Carbon, organic, total; CTD/Rosette; CTD-RO; DEPTH, sediment/rock; Dredge; DRG; East Siberian Sea; Element analyser CHN, LECO; Gas chromatography - Mass spectrometry (GC-MS); Giant box corer; GKG; Gravity corer (Kiel type); KAL; Kapitan Dranitsyn; Kara Sea; Kasten corer; KD9523-8; KD9529-12; KD9533-11; KD9541-13; KD9548-13; KD9565-12; KD9568-8; KD9572-1; Laptev Sea; MUC; MULT; MultiCorer; Paleoenvironmental Reconstructions from Marine Sediments @ AWI; Phytoplankton biomarker Brassicasterol IP25 index; Phytoplankton biomarker Dinosterol IP25 index; Polarstern; PS2721-1; PS2734-3; PS2735-5; PS2736-3; PS2740-8; PS2741-1; PS2743-7; PS2747-8; PS2767-6; PS2768-3; PS2774-2; PS2778-1; PS2780-5; PS2781-2; PS2791-5; PS36